2014
DOI: 10.1111/evo.12565
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic test of the Red Queen Hypothesis: Outcrossing and parasitism in the Nematode phylum

Abstract: Sexual outcrossing is costly relative to selfing and asexuality, yet it is ubiquitous in nature, a paradox that has long puzzled evolutionary biologists. The Red Queen Hypothesis argues that outcrossing is maintained by antagonistic interactions between host and parasites. Most tests of this hypothesis focus on the maintenance of outcrossing in hosts. The Red Queen makes an additional prediction that parasitic taxa are more likely to be outcrossing than their free-living relatives. We test this prediction in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 96 publications
(149 reference statements)
0
10
0
Order By: Relevance
“…It therefore predicts sexual taxa to dominate in habitats where parasite-host and/ or predator-prey interactions control community dynamics (Hamilton, 1980;Jaenike, 1978), which is often the case when predators/ parasites reach high densities (Ladle, 1992). A number of field and laboratory studies supported the RQT (Gibson & Fuentes, 2015;Haafke, Chakra, & Becks, 2016;Kotusz et al, 2014), but many are based on a single parasite-host system, the snail Potamogyrgus antipodarum and its trematode parasite (Jokela, Dybdahl, & Lively, 2009;King, Delph, Jokela, & Lively, 2009;Lively, 2010). A number of field and laboratory studies supported the RQT (Gibson & Fuentes, 2015;Haafke, Chakra, & Becks, 2016;Kotusz et al, 2014), but many are based on a single parasite-host system, the snail Potamogyrgus antipodarum and its trematode parasite (Jokela, Dybdahl, & Lively, 2009;King, Delph, Jokela, & Lively, 2009;Lively, 2010).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It therefore predicts sexual taxa to dominate in habitats where parasite-host and/ or predator-prey interactions control community dynamics (Hamilton, 1980;Jaenike, 1978), which is often the case when predators/ parasites reach high densities (Ladle, 1992). A number of field and laboratory studies supported the RQT (Gibson & Fuentes, 2015;Haafke, Chakra, & Becks, 2016;Kotusz et al, 2014), but many are based on a single parasite-host system, the snail Potamogyrgus antipodarum and its trematode parasite (Jokela, Dybdahl, & Lively, 2009;King, Delph, Jokela, & Lively, 2009;Lively, 2010). A number of field and laboratory studies supported the RQT (Gibson & Fuentes, 2015;Haafke, Chakra, & Becks, 2016;Kotusz et al, 2014), but many are based on a single parasite-host system, the snail Potamogyrgus antipodarum and its trematode parasite (Jokela, Dybdahl, & Lively, 2009;King, Delph, Jokela, & Lively, 2009;Lively, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…The RQT does not make explicit predictions on the effects of resource availability, but it has been suggested that small populations are less infested by parasites (Arneberg, Skorping, Grenfell, & Read, 1998) thereby weakening Red Queen processes. A number of field and laboratory studies supported the RQT (Gibson & Fuentes, 2015;Haafke, Chakra, & Becks, 2016;Kotusz et al, 2014), but many are based on a single parasite-host system, the snail Potamogyrgus antipodarum and its trematode parasite (Jokela, Dybdahl, & Lively, 2009;King, Delph, Jokela, & Lively, 2009;Lively, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated if uniparental reproduction is associated with lower or higher diversification rates. Taxa were classified following Gibson and Fuentes (2015) , in which male frequency was used as a proxy for mating system. Because the absence of males cannot distinguish parthenogenesis (asexuality) from androdioecy (mostly selfing), these two modes are treated as a single category of uniparental reproduction.…”
Section: Methodsmentioning
confidence: 99%
“…We used the phylogeny and character data originally reported in Gibson and Fuentes (2015) , which included a phylogenetic reconstruction of 2,700 postburn-in trees modified from Meldal et al. (2007) .…”
Section: Methodsmentioning
confidence: 99%
“…The topic of mating system evolution continually arises with the caenorhabditids, and with nematodes more in general. Mating system varies throughout the entire phylum, from obligate outcrossing to selfing to parthenogenesis (Bell, 1982;Denver et al, 2011;Gibson and Fuentes, 2015). Within the caenorhabditids, selfing has evolved multiple times from the ancestral state of obligate outcrossing (Kiontke et al, 2004;Kiontke and Fitch, 2005;Cutter et al, 2008).…”
Section: Do Coevolving Parasites Maintain Outcrossing?mentioning
confidence: 99%